Elementary statistics : - Bluman, Allan G. (McGraw-Hill, 2008)
Elementary Statistics: A Brief Version is written for students in the beginning statistics course whose mathematical background is limited to basic algebra. The book uses a nontheoretical approach in which concepts are explained intuitively and supported by examples for your student. There are no formal proofs in the book. The applications are general in nature and the exercises include problems from agriculture, biology, business, economics, education, psychology, engineering, medicine, sociology, and computer science. The learning system found in Elementary Statistics: A Brief Version provides your student with a valuable framework in which to learn and apply concepts!